Tailings Dam Performance : Modeling and Safety Analysis of a Tailings dam - Knutsson, Roger (Luleå tekniska universitet, Geoteknologi, 2015)
Storage and management of mine waste are both needed in the mining industry. After mineral extraction of the ore, there are generally leftovers with insufficient economical value that need to be taken care of. The finest grained fractions are referred to as tailings. Since every mine site and every tailings impoundment is unique, there is unfortunately not an universal answer to proper management that can be applied everywhere. Even though local guidelines and regulations can be considered to give a best practice in terms of design, there is correspondingly a need for dam safety stewardship on an operational level. Without such stewardship, not even the best designed dams or facilities would be fully controlled in terms of safety. Conversely, even badly designed dams can be operated in safe manners with good stewardship and surveillance programs. The coupling between design and stewardship is therefore important in order to reach proper tailingsmanagement.In the design of tailings dams, a certain value of the factor of safety for slopes of the dams is normally striven for to secure stability. The value is generally based on national regulations and/or guidelines. In Sweden the factor of safety should not be lower than 1.5 under normal conditions. In the guidelines, recommendations are often given on dam surveillance and field measurements of e.g. pore water pressure, deformations and seepage. Field measurements are taken, but are generally assessed in terms of trends (change with time) and not by comparison to anticipated performance.In this study, numerical modeling has been used for stability analyses and dam performance, as predictions of deformations and pore water pressure levels. An upstream tailings dam located in northern Sweden has been used as a case. The granular materials being part of the model based were described based upon geotechnical investigations (field and lab). The tailings material was modeled, on a constitutive level, by the Hardening Soil model. Good agreement betweensimulated behavior ...